A new section of Silene (Caryophyllaceae) including a new species from South Anatolia, Turkey - Aydin, Zeynep; Ertekin, Alaattin Selçuk; Långström, Elisabeth; Oxelman, Bengt (Phytotaxa, 2014)
Silene section Cryptoneurae (Caryophyllaceae) and S. ertekinii from Western Antalya, Turkey, are described as new taxa on the basis of morphological and molecular investigations. Nuclear ITS and chloroplast rps16 DNA sequences clearly support the recognition of the new section. Inclusiveness and characterization of the new section is discussed and described, and a key for the included species is provided. Diagnostic characters of the new species S. ertekinii are given and its relation to the other species of the section is discussed.